The Impact of Servant Leadership on Employee Performance Mediated by Employee Loyalty and Employee Satisfaction: A Case Study of PT. Garuda Totalindo Jaya - Willy Budi Wibowo; Risa Bhinekawati (International Journal of Business Studies, 2021)
This study aims to investigate the relationships among the variables of servant leadership, employee loyalty, employee satisfaction, and employee performance in the context of a family business in Indonesia. This study applies quantitative approach with empirical evidence obtained from the entire employees of PT. Garuda Totalindo Jaya, a family-owned supplier spare part company as the case study. For the analysis technique, this study uses Partial Least Square (PLS) Structural Equation Modeling (SEM) as a program to run the collected data from 71 respondents during the period of July 2019. The findings of the study show that servant leadership has positive impact on employee loyalty and employee satisfaction; employee satisfaction has positive impact on employee loyalty; and employee loyalty has positive impact on employee performance. This study expands the knowledge on human resources in the context of family business in Indonesia. It should be beneficial for both researcher and also the company itself. Moreover, it can give another exposure of the future research to study more variables in term of leadership.